Post Apartheid Metro Boundaries: Conflicts, Contestations and Compromises in Durban - (:unkn) unknown (My University, 2002)
Countries seeking to remake the structure of their societies have placed a strong emphasis on the development of a viable and effective system of local government. The restructuring of local government is especially significant in the context of South Africa's emerging democracy. A key component of this process has been boundary delimitation, which involved a process of spatial organisation and re-organisation. In South Africa the de-racialisation of local government represents a major challenge. Many affluent white local authorities were reluctant to give up the power and privileges of the old order and merge with previously black local authorities. Also, the socio-spatial distortions of the apartheid era need to be addressed through a more equitable distribution of resources, and the re-drawing of geographical boundaries. Attempts at municipal restructuring in South Africa have been fraught with problems and conflicts. The conflicts engendered, the negotiations, compromises, and coalitions generated constitute important areas of research. Examining and elucidating the manner in which these various forces have manifested themselves in the major metropolitan centres is the central theme of this paper. The focus of this paper is on boundary delimitation in the Durban Metropolitan area.
Keywords: African Research